Ornithology: the haunts and habits of birds - Dial, F. V. (My University, 1897)
Introduction: It is easy to understand the enthusiasm of ornithologists. The subjects of their study are found among the grandest and most beautiful scenes of nature. They pursue their investigations, not bending over the desk or stifled by the fumes of a laboratory, but beneath the open heavens, along the sea, by the side of water courses, through valleys, over hills, wherever the bird makes his home. Man’s thoughtlessness and greed have gone so far as to render extinct some of our North American birds during the present century, and others are threatened. This is often commented upon, and suggestions made to stop the work of destruction before it is too late; but nothing comes of it. The phrase “there are more gunners than birds” is often literally true and laws against their use have been passed, protecting especially certain species of birds. The ornithologist cannot wholly escape the just criticism in this matter of bird slaughter. It is not justifiable to kill a hundred birds in a day just to see if a particular one is among them; but if some scientific use is made of the dead birds, as in the practice of taxidermy work it would be better. A great many facts on the subject of birds and their place in nature have been collected, and thus the great science of Ornithology has been formed.
Citation: Dial, F. V. Ornithology: the haunts and habits of birds. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Ornithology; Birds; Habitat; Theses; Manuscripts (documents)